A cross-sectional study on knowledge, attitude and practices among diabetic patients about diabetes and its complications in Central Delhi - Ravinder Pal Singh; Megha Khobragade; Anil Kumar (MRIMS Journal of Health Sciences, 2013)
Background: Diabetes mellitus (DM) is now one of the most common non-communicable diseases globally. It is the fourth or fifth leading cause of death in most high-income countries and there is substantial evidence that it is epidemic in many economically developing and newly industrialized nations. The mortality due to diabetes is mostly due to its complication and the most effective way to prevent complications is to impart knowledge to patient so that they can practice for prevention of complication of diabetes. Objective: To assess the knowledge, attitude and practices of diabetic patients for diabetes and its complications. Methods: Data was collected using a pre-tested, validated questionnaire from a total of 170 patients attending diabetes clinic in Ram Monohar Lohia Hospital New Delhi. Results: Out of 170 patients, 91 (53.5 %) were female and 79(46.5 %) were male patients. In the study population 146 (85.9%) participants had the basic knowledge regarding what type of disorder diabetes is, and about 149 (87.6 %) participants in study population said that the know what to eat. The maximum knowledge was seen about eye problems 48.82 % and kidney problems 40%. Conclusion: There is still need for increase in IEC and BCC activity in term of campaigns on diabetic complication, awareness regarding foot care, regular exercise, and regular routine checkups.